2013
DOI: 10.2528/pier13021908
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Electromagnetic Absorption Towards Human Head Due to Variation of Its Dielectric Properties at 900, 1800 and 1900 MHZ With Different Antenna Substrates

Abstract: Abstract-This paper analyzes and discusses the effect of the electromagnetic absorption by human head against variation of head dielectric properties at 900, 1800 and 1900 MHz. The characteristics of helical antenna and its substrates with variation in human head dielectric properties are simulated by implementing finite-difference time-domain (FDTD) method using CST Microwave studio. The variations in human head dielectric properties were manipulated by increasing and decreasing 10% and 20% of each of the hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…The drawback of this model is the shape and size of the Ear changes and evaluation done on a particular phantom with dipole antenna is added disadvantage. Husni et al analyzed the effect of metallic earing on antenna performance and have observed peak SAR increases due to field scattering, and redistribution of RF energy occurs. The dipole antenna without shielding is again a setback in this analysis.…”
Section: Exposure Areasmentioning
confidence: 99%
“…The drawback of this model is the shape and size of the Ear changes and evaluation done on a particular phantom with dipole antenna is added disadvantage. Husni et al analyzed the effect of metallic earing on antenna performance and have observed peak SAR increases due to field scattering, and redistribution of RF energy occurs. The dipole antenna without shielding is again a setback in this analysis.…”
Section: Exposure Areasmentioning
confidence: 99%
“…The permittivity, conductivity and mass density of the homogeneous human head at 900 MHz and 1800 MHz are given in Table 2 [7]. To consider the effects of head the antenna is placed at a certain distance (say S mm) from the head as shown in Fig.…”
Section: Modelling Of a Homogenous Human Headmentioning
confidence: 99%
“…It is usually averaged either over a small volume of tissue (1 g or 10 g) or over the whole body. In USA, the SAR limit is specified as 1.6 W/kg, averaged over 1 g of tissue and in Europe and Japan, the SAR limits are specified as 2.0 W/kg, averaged over 10 g of tissue [7]. In [8] SAR evaluations of a dipole antenna for different frequencies are shown and compared with the safety limit.…”
Section: Introductionmentioning
confidence: 99%
“…There are various sources of uncertainty and variation in this kind of combined FDTD and temperature simulations [5][6][7][8][9][10][11][12][13][14][15][16]. Usually, the rise in temperature has been small so thermoregulatory response has been ignored, which may have led to overestimation.…”
Section: Introductionmentioning
confidence: 99%